Seropersistence of SII-ChAdOx1 nCoV-19 (COVID-19 vaccine): 6-month follow-up of a randomized, controlled, observer-blind, phase 2/3 immuno-bridging study in Indian adults - Prasad S. Kulkarni; Chandrasekaran Padmapriyadarsini; Johan Vekemans; Ashish Bavdekar; Madhu Gupta; Praveen Kulkarni; B.S. Garg; Nithya J. Gogtay; Muralidhar Tambe; Sanjay Lalwani; Kiranjit Singh; Renuka Munshi; et al. (Human Vaccines & Immunotherapeutics, 2024)
ABSTRACTAZD1222 (ChAdOx1 nCoV-19) is a replication-deficient adenoviral vectored coronavirus disease-19 (COVID-19) vaccine that is manufactured as SII-ChAdOx1 nCoV-19 by the Serum Institute of India Pvt Ltd following technology transfer from Oxford University/AstraZeneca. The non-inferiority of SII-ChAdOx1 nCoV-19 with AZD1222 was previously demonstrated in an observer-blind, phase 2/3 immuno-bridging study (trial registration: CTRI/2020/08/027170). In this analysis of immunogenicity and safety data 6 months post first vaccination (Day 180), 1,601 participants were randomized 3:1 to SII-ChAdOx1 nCoV-19 or AZD1222 (immunogenicity/reactogenicity cohort n = 401) and 3:1 to SII-ChAdOx1 nCoV-19 or placebo (safety cohort n = 1,200). Immunogenicity was measured by anti-severe acute respiratory syndrome coronavirus 2 spike (anti-S) binding immunoglobulin G and neutralizing antibody (nAb) titers. A decline in anti-S titers was observed in both vaccine groups, albeit with a greater decline in SII-ChAdOx1 nCoV-19 vaccinees (geometric mean titer [GMT] ratio [95% confidence interval (CI) of SII-ChAdOx1 nCoV-19 to AZD1222]: 0.60 [0.41–0.87]). Consistent similar decreases in nAb titers were observed between vaccine groups (GMT ratio [95% CI]: 0.88 [0.44–1.73]). No cases of severe COVID-19 were reported following vaccination, while one case was observed in the placebo group. No causally related serious adverse events were reported through 180 days. No thromboembolic or autoimmune adverse events of special interest were reported. Collectively, these data illustrate that SII-ChAdOx1 nCoV-19 maintained a high level of immunogenicity 6 months post-vaccination. SII-ChAdOx1 nCoV-19 was safe and well tolerated.